Effects of Business Recovery Strategies on Seismic Risk and Cost-Effectiveness of Structural Retrofitting for Business Enterprises. Issue 4 (November 2019) - Donà, Marco; Bizzaro, Luca; Carturan, Federico; da Porto, Francesca
Recent earthquakes in Italy have significantly affected productive activities, particularly in business interruption (BI) and, consequently, heavy losses for companies, highlighting the need for appropriate seismic risk assessment and management. To estimate seismic risk accurately, both direct (repair/replacement) and indirect (BI) losses must be quantified. Companies' balance sheets can be used to estimate BI losses, which, however, are very sensitive to business recovery strategies (BRSs) devised by corporate managers after the seismic event. The aim of this study is to evaluate the effects of BRSs on seismic risk estimates and consequently on structural retrofitting cost-effectiveness. A loss model (including direct and indirect costs and BRS effects) was defined, based on a real-life case study (a biomedical packaging company that was damaged by the 2012 Italian earthquake but recovered soon after) and was used in parametric risk analyses assessing several types of company vulnerabilities and seismic hazards. In areas with low-to-moderate seismicity, seismic retrofitting of existing reinforced concrete factories may be justified or otherwise, depending on whether BRSs are considered or not.